Peran Etika Bisnis dalam Membangun Kepercayaan Konsumen - Mega Hasibuan; Zuhrinal M Nawawi (Lembaga Pengembangan Kinerja Dosen, 2024)
In terms of establishing relationships with other parties in the business world, ethics play an important role. Business ethics play an important role in determining the success or failure of a business. The purpose of this study is to determine and analyze the role of business ethics in building consumer trust. The research method used is the Systematic Literature Review (SLR) method on journals that have been published from 2014 to 2023. The results of this study indicate that the role of business ethics has a significant influence in building consumer trust.